La actividad extraterritorial de la Administración Pública: un acercamiento a los actos administrativos transnacionales - Vignolo Cueva, Giancarlo (2022)
In this paper the author reflects and analyzes the Peruvian regulation and the existing national and foreign doctrine on transnational administrative acts, whether they have been issued by a Peruvian or a foreign Public Administration, and whether or not they are valid and effective in the legal systems where they were not issued. Finally, it raises the possibility of an ad intra normative review both at the legal level and in international treaties.